The relationship between surname frequency and Y chromosome variation in Spain. - Martinez-Cadenas, C; Blanco-Verea, A; Hernando, B; Busby, G; Brion, M; Carracedo, A; Salas, A; Capelli, C (Nature Publishing Group, 2015)
In most societies, surnames are passed down from fathers to sons, just like the Y chromosome. It follows that, theoretically, men sharing the same surnames would also be expected to share related Y chromosomes. Previous investigations have explored such relationships, but so far, the only detailed studies that have been conducted are on samples from the British Isles. In order to provide additional insights into the correlation between surnames and Y chromosomes, we focused on the Spanish population by analysing Y chromosomes from 2121 male volunteers representing 37 surnames. The results suggest that the degree of coancestry within Spanish surnames is highly dependent on surname frequency, in overall agreement with British but not Irish surname studies. Furthermore, a reanalysis of comparative data for all three populations showed that Irish surnames have much greater and older surname descent clusters than Spanish and British ones, suggesting that Irish surnames may have considerably earlier origins than Spanish or British ones. Overall, despite closer geographical ties between Ireland and Britain, our analysis points to substantial similarities in surname origin and development between Britain and Spain, while possibly hinting at unique demographic or social events shaping Irish surname foundation and development.